Dissociated Pmch and Cre Expression in Lactating Pmch-Cre BAC Transgenic Mice - Bethany G. Beekly; Bethany G. Beekly; William C. Frankel; William C. Frankel; Tova Berg; Susan J. Allen; David Garcia-Galiano; Giancarlo Vanini; Giancarlo Vanini; Carol F. Elias; Carol F. Elias; Carol F. Elias (Frontiers Media S.A., 2020)
The melanin-concentrating hormone (MCH) system plays a role in many physiological processes including reproduction and lactation. However, research regarding the function of MCH on different aspects of the reproductive function lags, due in part to a lack of validated genetic models with which to interrogate the system. This is particularly true in the case of female reproduction, as the anatomy and function of the MCH system is not well-characterized in the female mouse. We set out to determine whether the commercially available Pmch-Cre transgenic mouse line is a viable model to study the role of MCH neurons in distinct female reproductive states. We found that Pmch is transiently expressed in several nuclei of the rostral forebrain at the end of lactation. This includes the medial subdivision of the medial preoptic nucleus, the paraventricular nucleus of the hypothalamus, the ventral subdivision of the lateral septum, the anterodorsal preoptic nucleus and the anterodorsal nucleus of the thalamus. The Pmch expression in these sites, however, does not reliably induce Cre expression in the Pmch-Cre (BAC) transgenic mouse, making this line an inadequate model with which to study the role of MCH in behavioral and/or neuroendocrine adaptations of lactation. We also contribute to the general knowledge of the anatomy of the murine MCH system by showing that lactation-induced Pmch expression in the rostral forebrain is mostly observed in GABAergic (VGAT) neurons, in contrast to the typical MCH neurons of the tuberal and posterior hypothalamus which are glutamatergic (VGLUT2).